2013
DOI: 10.1002/agr.21333
|View full text |Cite
|
Sign up to set email alerts
|

Oligopoly and Price Transmission in Turkey's Fluid Milk Market

Abstract: Farmers and consumers suspect that processing firms abuse their power in the milk marketing chain by engaging in price fixing behavior. The author employs threshold autoregressive and moment threshold autoregressive tests, and contrary to expectations, finds evidence for a downward trend in wholesale milk price without a corresponding decline in farm-gate prices. The downward trend coincides with increased competition in the dairy industry and with the growing market share of the formal sector at the expense o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
0
5
0
4
Order By: Relevance
“…Several recent agricultural commodity price transmission and market integration studies have focused on price relationships among markets for which trade regularly occurs (see the methodological development and worldwide empirical evidence of agricultural commodity price transmission in Brosig et al (2011), Abbassi et al (2012), Tekgüç (2013), Acosta et al (2014), Santeramo (2015), Cacchiarelli et al (2016), Tifaoui and Von Cramon‐Taubadel (2017), and Yu and Gould (2019)). Most of these studies have a similar underlying theoretical competitive spatial equilibrium framework, which is described thoroughly by Lence et al (2018).…”
Section: Literature Review: Price Transmission With Growing Conditions Variation and Sparse Market Informationmentioning
confidence: 99%
“…Several recent agricultural commodity price transmission and market integration studies have focused on price relationships among markets for which trade regularly occurs (see the methodological development and worldwide empirical evidence of agricultural commodity price transmission in Brosig et al (2011), Abbassi et al (2012), Tekgüç (2013), Acosta et al (2014), Santeramo (2015), Cacchiarelli et al (2016), Tifaoui and Von Cramon‐Taubadel (2017), and Yu and Gould (2019)). Most of these studies have a similar underlying theoretical competitive spatial equilibrium framework, which is described thoroughly by Lence et al (2018).…”
Section: Literature Review: Price Transmission With Growing Conditions Variation and Sparse Market Informationmentioning
confidence: 99%
“…Milk is considered as a strategically important commodity in Turkey (Günden, Bilgic, Miran & Karli 2011). Due to economies of scale in this growing market, Turkish dairy processing firms continue to be profitable (Tekgüç, 2013). According to State Institute of Statistics, in 2017 total raw milk production almost exceeds 20 million tons (TÜİK, 2018a) and İzmir province takes the second place in Turkey with nearly 1 million ton production (TÜİK, 2018b).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Threshold Autoregressive (TAR) model was first discussed by Tong () and later revisited by Enders and Granger (), who introduced a model variation, the Momentum‐TAR (M‐TAR), increasing the model's popularity since then (for recent research in agricultural economics applying a TAR framework, see Abdulai, ; Awokuse & Wang, ; Goychuk & Meyers, ; Han , Chung, & Surathkal, ; Lee & Gómez, ; Simioni et al., ; Surathkal, Chung, & Sungill, ; Tekgüç, , among others). Engle and Granger () showed that when two variables are cointegrated, an Error Correction Model (ECM) can be specified as 0truenormalΔp1t=Φj0.33em()p2,0.33emt1β0β1p2,t1+i=1k1ΓinormalΔp1,ti+i=1k1δinormalΔp2,ti+εt0.16em,where pi,t,i=1,2 are prices at two different levels of the supply chain, β 0 is a constant term, the term inside the brackets specifies the error correction mechanism (i.e., ECT), Γi and δi are matrices of short‐run parameters estimating the effect of shocks on Δpi,t, and εt is a disturbance term i.i.d. WN (0,0.33emσ2).…”
Section: Modeling Asymmetric Price Transmissionmentioning
confidence: 99%
“…(); Busse, Brümmer, and Ihle (); Conforti (); Goychuk and Meyers (); Hassouneh, Serra, Bojnec, and Gil (); Listorti and Esposti (); Simioni et al. (); Tekgüç (); and Verreth et al. ().…”
mentioning
confidence: 99%